CONJUGAL VISIT DALAM PERSPEKTIF TEORI RELATIF SISTEM PEMIDANAAN DI INDONESIA - Hidayat, Tengku Arif; Anandan, Tara Raf; Putri, Nada Marenza; Silitonga, Rheinhard Goklas; Wijaya, Winston (Universitas Wiralodra, 2023)
Imprisonment as a struggle for liberty should only limit the prisoner's right to freedom. This interpretation emerged along with the paradigm shift of punishment from punishment as a form of retaliation to punishment as a form of formation and recovery. This shift in rules by experts is often called relative theory which will certainly have consequences for the modification of the penal system itself. the fulfillment of other rights of prisoners must be guaranteed, including the right to sexual needs, globally, it is known as Conjugal Visit. Several countries in the world have actualized the fulfillment of this right. Indonesia itself until now has not regulated conjugal visits in its correctional system. There are various reasons why this visit has not been properly actualized in Indonesia, such as overcapacity and lack of facilities and resources. The pros and cons related to the procurement of conjugal visits became the basis for the author to compile this study. This legal research seeks to analyze the possibility of implementing this visit in Indonesia, its urgency, weaknesses and solutions that can be accommodated by the government as the implementer of the correctional system. Legal research using empirical analysis methods. this legal research ultimately concludes that, the procurement of conjugal visits in Indonesia has its own urgency and is in the process of being realized. Although there are contradictions and various issues that will arise in its application, this visit is considered in accordance with contemporary penal rules related to relative theory.